The Judge’s Decision on Rejection of Polygamous Marriage Proposal in Sadd adz-Dzari'ah Perspective - Mahmudi, Zaenul; Khaira, Thariqul (Sakina: Journal of Family Studies, 2022)
Polygamy is permitted in Islamic law and also in Indonesian marriage law when fulfilled the requirements. In decision number 280/Pdt.G/2020/PA.Sbh the application for a polygamy permit was rejected by the Judges, despite the fact that the first wife had granted permission for polygamy and the husband had met the polygamy requirements. As a result, the focus of this research is on discussing the Judge’s considerations then analyzing them using sadd adz-dzari’ah. This is normative research using a case approach, and it is carried out by tracing, searching, and reviewing materials in the form of decisions, laws, books, journals, and other sources related to polygamy and sadd adz-dzari’ah. The Judges rejected the case because the application for a polygamy permit do not comply with Law numbern1nof 1974, and Lawnnumbern9nofn1975. Sadd adz-dzari’ah states that whether the case is accepted or rejected, both contain mafsadah. The differences are in the mafsadah’s quality; if the case is accepted, the mafsadah’s quality is qath’i. Whereas if the case is rejected, the mafsadah’s quality is ghalib. Closing the definite mafsadah takes precedence, so this case is better rejected based on the sadd adz-dzari’ah analysis because the quality of the mafsadah is lower.